Tracking Inner City Substance Users from the ED: How many Contacts Does It Take? - Cunningham, Rebecca (2008)
Longitudinal studies of substance users report difficulty in locating and completing 12-month interviews, which may compromise study validity. OBJECTIVE: This study examined rates and predictors of contact difficulty and in-person follow-up completion among patients presenting with cocaine-related chest pain to an inner-city ED. We hypothesize less staff effort in contacting patients and lower follow-up rates would bias subsequent substance use analysis by missing those with heavier substance misuse. METHODS: 219 patients 19-60 yrs (65% males; 78% African-American) with cocaine related chest pain were interviewed in the ED, and then in person at 3, 6, and 12-months. Demographics, substance use measures, and amount/type of research staff contacts (telephone, letters, home visits, and locating patient during return ED visits) were recorded. Linear regression analyses were conducted to predict quantity of patient contacts for the 12-month follow-up. RESULTS: Interview completion rates at 3, 6 and 12-months were: 78%, 82%, and 80%. Average contact attempts to obtain each interview were: 10 at 3-months (range 3-44), 8 at 6-months (1-31), and 8 at 12-months (1-50); 13% of patients required a home visit to complete the 12 month interview. Participants requiring more contact attempts by staff reported frequent binge drinking at baseline (p<.01) and were more likely to report prior mental health treatment (p<.05). Findings demonstrate that substantial staff effort is required to achieve adequate retention over 12- months of patients with substance misuse. Without these extensive efforts participants with a history of binge drinking would be missed at follow-up biasing longitudinal analyses.